Photo Editing Courses: Pemanfaatan Professional Graphic Design Software Dalam Mentransfer Editing Skills Dengan Mengadopsi Teknik TPS - Zuhri, Al; Agus Pratama; Husna, Fathayatul; Nova, Mirza Adia; Syam, Futry; Maulida Khairani; Havia Balqis Harahap; Fathia Rizki Amelia; Wira Siti Anisah Berutu; Syafitri Najmunnisa; Syarifah Uswatun Miswar (MEUSEURAYA - Jurnal Pengabdian Masyarakat, 2024)
One of the important hard skills to learn in the current Society 5.0 era is the ability to operate computer devices with software and features such as Adobe Photoshop which can facilitate photo editing. Photo editing skills are worth learning by students because they can bring benefits and value. To make it easier for students to understand the material, the team used a training method with the Think Pair Share (TPS) technique combined with pre-test and post-test instruments as a measuring tool to review and assess the development or changes in students' knowledge and understanding before and after dedication is carried out. The final results obtained from the pre-test and post-test show that after the students participated in this activity their knowledge increased regarding graphic design in general and photo editing in particular. Keywords: Graphic Design, Hard Skill, Photo Editing